PERJANJIAN KREDIT ANTARA BANK DENGAN PELAKU USAHA KECIL DAN MENENGAH DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT: Ahmad Munawir Siregar - admin, admin (Reformasi Hukum, 2019)
Many small and medium business actors (UKM) in Indonesia still find it difficult to get capital from banks, because they do not understand the contents of the agreement and do not have collateral. The formulation of this research problem is how the credit agreement between the bank and SME actors, and the purpose of the study is to obtain information about the credit agreement between the bank and the actor. Use can provide information to Small and Medium Enterprises (SMEs) Research methods are normative juridical. The results showed that the implementation of the agreement carried out by BRI KCP Jati Asih could not be separated from the provisions of the Civil Code. Even though the credit agreement is not clearly regulated in the Civil Code, but the elements of the credit agreement cannot be separated from the provisions contained in the Civil Code. The agreement entered into by the bank with SMEs uses a standard contract. With a standard agreement, there is an imbalance in the position between the bank and the debtor, and also the clauses in the agreement are burdensome to the debtor. The conclusion that in the implementation of bank credit always follows the principle of prudence, this is to prevent bad credit. To foster and enhance these beliefs, banks always use the 5C principle analysis, namely character, capacity, capital, collateral and condition of economy.